Analysis of Guest Room Service by Room Attendants in the Housekeeping Department - Ayu Suriyani, Ni Nyoman; Darma Susila, I Made Gede; Suwitra Wirya, I Made (Akademi Komunitas MAPINDO, 2023)
Good or bad service of this room section or often called room attendant in affecting guest satisfaction directly.This is because this product is sought after by guests staying at the hotel so that the service requires specialattention. The purpose of this study is to see the general description of hotel room service and changes inphysical services that occur in hotel room service by room attendants from the past to the present. A qualitativedescriptive approach was used based on data collected through observation, literature studies and interviewswith chamber attendants, supervisors and executive housekeepers. The data analysis technique used isqualitative analysis by paying attention to reduction data, display data, and verification data. The concept ofSOP (Standard Operating Procedure) housekeeping service, room attendant service, and traveler satisfactionconcept are used in the analysis to process information about the current condition of room service by roomattendants. The results show that there are some physical service changes that occur in room service accordingto guest requests. Room service currently has several changes due to technological developments so that hotelsneed to adjust to some of the physical services that have been provided before.Keywords: Room analysis, tourist satisfaction, housekeeping department, room attendant